INTEGRASI REMEDIASI MISKONSEPSI DALAM PEMBELAJARAN DENGAN PENDEKATAN KONFLIK KOGNITIF PADA MATERI TEKANAN - Hermawati, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractThe aims of this research was determine the effect of integrated remediation misconception in learning with cognitive conflict approach to decreasing the number of student misconception on Pressure material in MTs Negeri Bakau. The research used pre-experimental design with one group pre-test post-test design. Diagnostic test which consist of 9 multiple choice question with open reasoning was used as research instrument to asses the number of students misconception. Thirty-five students from VIII B participant in the research as a sample by intact group technique. Based on the result, the decrease of misconception student for each concept is 71,68% and the decrease of misconception for each student equal to 71,22% . The effect size of DQM (The Decreasing of Quantity of the student that Misconceptions) equal to 71,28%. Integrated remediation misconception activitiesÂ  in learning with cognitive conflict approach are expected to be used as an alternative remediation activity in order to overcome misconceptions experienced by students.Keyword: Remedy, misconception, integrated, cognitive conflict, pressure